Competition as a Catalyst for Innovation? Assessing SMEs’ Attitudes towards Digital Market Regulation and Competition (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Expanding the digital economy represents a major challenge for EU competition policy and regulations. Despite their importance, small and medium-sized enterprises (SMEs) receive minimal attention regarding their perspectives on the issue. Hence, the main aim of the paper is to examine their attitudes towards digital market competition and its regulations. The paper analyses secondary data from the Flash Eurobarometer 510 survey with more than 12,800 observations from EU countries. Moreover, it also identifies potential factors affecting firms’ attitudes based on the logistic regression. Firms’ attitudes seem to be correlated with awareness of the EU competition policies for digital transition. Better-informed firms have more favourable attitudes towards market competition. They are increasingly perceiving competition as a catalyst for innovation. Moreover, they are increasingly reporting significant problems with the lack of competition when applying to digital platforms for customer outreach. Insufficient competition in the digital market appears to be a problem for a significant proportion of SMEs’. We also identified the sectors and countries experiencing the worst problems associated with limited competition in the digital platform market. Smaller firms and those with a long presence on the market are more supportive of the Digital Markets Act as an effective regulation.